2023
DOI: 10.1186/s12887-023-04265-x
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of risk factors of precocious puberty in children

Yan Dong,
Lili Dai,
Yang Dong
et al.

Abstract: Background The purpose of this study is to explore the related factors of precocious puberty in children. Methods 1239 children who underwent physical examination in our hospital from January 2020 to December 2022 were analyzed, including 198 precocious children and 1041 normal children. According to the age of 198 precocious children and 1041 normal children, 205 normal children were selected, and the remaining 836 normal children were excluded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These findings suggest that early detection of excessive weight gain, especially during infancy, maybe essential to prevent future CPP in girls. However, obesity is not the only risk factor associated with early onset of puberty (15). Here, Tang et al showed that after adjustment of BMI, dietary patterns, soft drink, feeding pattern and mother's BMI, short sleep duration, were all associated with early pubertal development in both girls and boys.…”
Section: Early Obesity and Hormonal Interactionsmentioning
confidence: 85%
See 1 more Smart Citation
“…These findings suggest that early detection of excessive weight gain, especially during infancy, maybe essential to prevent future CPP in girls. However, obesity is not the only risk factor associated with early onset of puberty (15). Here, Tang et al showed that after adjustment of BMI, dietary patterns, soft drink, feeding pattern and mother's BMI, short sleep duration, were all associated with early pubertal development in both girls and boys.…”
Section: Early Obesity and Hormonal Interactionsmentioning
confidence: 85%
“…These findings suggest that early detection of excessive weight gain, especially during infancy, maybe essential to prevent future CPP in girls. However, obesity is not the only risk factor associated with early onset of puberty ( 15 ). Here, Tang et al.…”
Section: Early Obesity and Hormonal Interactionsmentioning
confidence: 99%